2019
DOI: 10.3390/jcm9010009
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Action of Heterogeneous Nuclear Ribonucleoprotein A2/B1 in Patients with Autoimmune Endocrine Disorders

Abstract: Our previous studies documented that human fibroblast-limbal stem cells (f-LSCs) possess immunosuppressive capabilities, playing a role in regulating T-cell activity. This study highlights the molecular activities by which human f-LSCs can attenuate the inflammatory responses of self-reactive peripheral blood mononuclear cells (PBMCs) collected from patients with autoimmune endocrine diseases (AEDs). Anti-CD3 activated PBMCs from twenty healthy donors and fifty-two patients with AEDs were cocultured on f-LSC m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The electrophoretic separation was performed on 18 cm long strips with a pH range of 3–10. The strips were then equilibrated in a solution containing 50 mM Tris-HCl pH 6.8, 6 M urea, 0.5% SDS, 30% Glycerol, 130 mM DTE and 135 mM Iodoacetamide and then separated on 9–16% linear gradient polyacrylamide gels (SDS-PAGE), with a constant current of 20 mA/gel, as previously described [ 34 , 35 , 36 ]. The gels were silver stained and analyzed with the dedicated Image-Master 2D Platinum software.…”
Section: Methodsmentioning
confidence: 99%
“…The electrophoretic separation was performed on 18 cm long strips with a pH range of 3–10. The strips were then equilibrated in a solution containing 50 mM Tris-HCl pH 6.8, 6 M urea, 0.5% SDS, 30% Glycerol, 130 mM DTE and 135 mM Iodoacetamide and then separated on 9–16% linear gradient polyacrylamide gels (SDS-PAGE), with a constant current of 20 mA/gel, as previously described [ 34 , 35 , 36 ]. The gels were silver stained and analyzed with the dedicated Image-Master 2D Platinum software.…”
Section: Methodsmentioning
confidence: 99%
“…After homogenization with 50 mM Tris-HCl pH 7.5, 0.003% penicillin, 0.005% streptomycin, tissue lysates were incubated under rotation overnight at 4 • C [44], and then centrifuged several times at 10,000 rpm for 20 min to remove cell debris. Bradford assay was used to quantify protein content, as already reported [34,[45][46][47][48]. Blood, collected into plastic tubes without coagulation accelerators to prevent the release of gelatinases during platelet activation, was centrifuged at 1600× g for 10 min 30 min after collection.…”
Section: Tissue and Sera Samples From Crc Patientsmentioning
confidence: 99%
“…Hence, FAM76B may have functions related to nuclear speckles, such as splicing factor storage and modification (Salichs et al 2009; McGlincy et al 2010). We found in this study that FAM76B interacts with hnRNPA2B1, a heterogeneous nuclear ribonucleoprotein related to mRNA binding and splicing (Peng et al 2021; Moran-Jones et al 2005) that is associated with inflammation (Lin et al 2020; Chen et al 2020; Coppola et al 2019; Hoffmann et al 2011). By in vitro and in vivo experiments, we showed that FAM76B could regulate NF-κB mediated inflammation by influencing the translocation of hnRNPA2B1.…”
Section: Discussionmentioning
confidence: 72%